Epidermal Structure and Phytochemical Screening of Palm Leaves (Family Arecaceae) - Husnudin, Uni Baroroh; Ekasari, Munifilia; Erliana, Dina; Setiyaningrum, Dewi A; Firdaus, Widani (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
The epidermal structure and phytochemical composition of six palm species (Arecaceae) were studied to understand their anatomical characteristics and bioactive compound content. Leaf samples from phoenix palm (Phoenix roebelenii), red palm (Cyrtostachys renda), foxtail palm (Wodyetia bifurcata), fan palm (Livistona chinensis), christmas palm (Adonidia merrillii), and yellow palm (Chrysalldocarpus lutescens) were analyzed through microscopic observation and phytochemical screening. The results revealed variations in epidermal cell shape, cell wall structure, and stomatal distribution. Most species exhibited smooth-walled epidermal cells, except for red palm (C. renda), which had wavy cell walls. Stomata were predominantly tetracytic, with red palm (C. renda) and christmas palm (A. merrillii) displaying an amphistomatic distribution, while the other species were hypostomatic. Phytochemical analysis revealed the presence of flavonoids and saponins in all samples. Triterpenoids were detected only in phoenix palm (P. roebelenii), fan palm (L. chinensis), and yellow palm (C. lutescens). Alkaloids were found in phoenix palm (P. roebelenii) and red palm (C. renda), while steroids were present in red palm (C. renda), foxtail palm (W. bifurcata), and christmas palm (A. merrillii). Additionally, tannins were detected in all plant samples except for fan palm (L. chinensis). These findings suggest that palm leaves possess significant bioactive compounds that could be explored for pharmaceutical and industrial applications.